ANALISIS POLA PEMBELIAN KONSUMEN BERDASARKAN DATA HISTORIS DENGAN METODE ASOSIASI DI PT EXCELLINDO PERKASA - Oktavia, Ganefa; Amrizal (Computer Science and Industrial Engineering, 2024)
This research aims to analyze consumer purchasing pattern based on historical data using association methods at PT Excellindo Perkasa, a company in the industrial sector. The primary focus is to enhance understanding of consumer preferences and purchasing habits for improving marketing efficiency and sales strategis. Association methods such as Apriori or FP Growth will be applied to historical consumer transaction data to identify relationship among products or services. The research steps include data collection, preprocessing to clean invalid data, application of association algorithms, and analysis of results to reveal purchasing patterns. The anticipated outcomes aim to provide valuable insights to PT Excellindo Perkasa, strengthening strategic decision-making, optimizing product inventory, and enhancing consumer satisfaction. Additionally, the study serves as a foundation for further research in consumer data analysis and marketing, supporting the development of better business strategies..